Genetic determinants of skin ageing: a systematic review and meta-analysis of genome-wide association studies and candidate genes - Chloe Wong; Jun Yan Ng; Yang Yie Sio; Fook Tim Chew (Journal of Physiological Anthropology)
Abstract Background Skin ageing is influenced by complex genetic factors. Various phenotypes such as wrinkling, pigmentation changes, and skin cancers have been linked to specific genetic loci. However, the underlying genetic mechanisms and pathways remain poorly understood. This systematic review and meta-analysis aims to summarise the genetic loci found to be associated with skin ageing phenotypes by published genome-wide association studies (GWAS) and candidate gene studies. We also evaluated the overall association of loci via meta-analysis and identified the association patterns to explore potential biological pathways contributing to skin ageing. The Web of Science, Embase, and PubMed databases were searched on January 2024 using specific exclusion criteria (e.g., study of non-human subjects, focus on skin diseases, or treatments) to identify relevant articles. There did not appear to be any significant publication bias observed across the all phenotypes. Main body A total of 48 studies were included, revealing 30 loci that were confirmed to be associated with skin ageing by multiple studies (e.g., AFG3L1P: odds ratio 1.133 95% confidence interval [1.044, 1.222]; BPIFA3: 1.859 [1.567, 2.151]; CLPTML1: 1.164 [1.0.99, 1.229]; CPNE7: 0.905 [0.852–0.958]; DEF8: 1.186 [1.042, 1.331]; IRF4: 1.260 [1.025, 1.495]; MYO16: 2.303 [1.697, 2.908]; PRDM16: 1.105 [1.084, 1.127]; RORA: 1.391 [1.206, 1.577]; SPG7: 0.922 [0.897, 0.947]; SPON1: 2.214 [1.204, 3.225]; SPTLC1: 1.464 [1.432, 1.495]; TYR: 1.175 [1.007, 1.343]). The lack of significance for many loci may be due to studies analysing different SNPs within the same locus, weakening the overall associations. Several loci were associated with specific phenotypic categories (e.g., skin colour related, skin cancer related, wrinkling and sagging related), suggesting shared biological pathways are involved in the pathogenesis of different skin ageing phenotypes. This pattern was also observed in several of the loci that do not have a significant overall association with skin ageing. Conclusion Despite significant heterogeneity among the included studies and the use of subjective visual methods for phenotype assessment, our review highlights the critical role of fundamental biological processes, such as development and cellular organisation, in skin ageing. Future research that targets the same SNP across multiple populations could strengthen the association of additional loci with skin ageing. Further investigation into these underlying biological processes would significantly advance our understanding of the pathogenesis of skin ageing phenotypes.